Cardiovascular Ultrasound - Sicari, Rosa
Cardiovascular Ultrasound is an online journal, publishing peer-reviewed: original research; authoritative reviews; case reports on challenging and/or unusual diagnostic aspects; and expert opinions on new techniques and technologies. We are particularly interested in articles that include relevant images or video files, which provide an additional dimension to published articles and enhance understanding. As an open access journal, Cardiovascular Ultrasound ensures high visibility for authors in addition to providing an up-to-date and freely available resource for the community. The journal welcomes discussion, and provides a forum for publishing opinion and debate ranging from biology to engineering to clinical echocardiography, with both speed and versatility.